Asian noodles : science, technology, and processing - Hou, Gary G. (Hoboken, N.J. : John Wiley & Sons, 2010)
In Asian Noodles: Science, Technology and Processing, international experts review the current knowledge and offer comprehensive cutting-edge coverage on Asian noodles unmatchable in any publication. The authors cover an array of topics including breeding for noodle wheat, noodle flour milling, noodle flour quality control and analysis, noodle processing, sensory and instrumental measurements of noodle quality, the effects of wheat factors on noodle quality, packaging and storage, nutritional fortification of noodle products, noodle flavor seasoning, and noodle plant setup and management.
Frontmatter -- Color Plates -- Breeding Noodle Wheat in China / Zhonghu He, Xianchun Xia, Yan Zhang -- Breeding for Dual-Purpose Hard White Wheat in the United States: Noodles and Pan Bread / Arron H Carter, Carl A Walker, Kimberlee K Kidwell -- Wheat Milling and Flour Quality Analysis for Noodles in Japan / Hideki Okusu, Syunsuke Otsubo, James Dexter -- Wheat Milling and Flour Quality Analysis for Noodles in Taiwan / C C Chen, Shu-Ying (Sophia) Yang -- Noodle Processing Technology / Gary G Hou, Syunsuke Otsubo, Hideki Okusu, Lanbin Shen -- Instant Noodle Seasonings / Kerry Fabrizio, Rajesh Potineni, Kim Gray -- Packaging of Noodle Products / Qingyue Ling -- Laboratory Pilot-Scale Asian Noodle Manufacturing and Evaluation Protocols / Gary G Hou -- Objective Evaluation of Noodles / David W Hatcher -- Sensory Evaluation of Noodles / Bin Xiao Fu, Linda Malcolmson -- Effects of Flour Protein and Starch on Noodle Quality / Byung-Kee Baik -- Effects of Polyphenol Oxidase on Noodle Color: Mechanisms, Measurement, and Improvement / E Patrick Fuerst, James V Anderson, Craig F Morris -- Effects of Flour Characteristics on Noodle Texture / Andrew S Ross, Graham B Crosbie -- Noodle Plant Setup and Resource Management / Gary G Hou, Syunsuke Otsubo, Verónica Jiménez Montaño, Julio González -- Quality Assurance Programs for Instant Noodle Production / Sumonrut Kamolchote, Toh Tian Seng, Julio González, Gary G Hou -- Rice and Starch-Based Noodles / Zhan-Hui Lu, Lilia S Collado.
Includes bibliographical references and index.
Description based on print version record.
Keywords: Noodles -- Asia; Wheat -- Milling -- Asia; Wheat -- Processing -- Asia; Noodles; Wheat -- Milling; Wheat -- Processing; Asia; Chemical engineering; Engineering; TECHNOLOGY & ENGINEERING -- Food Science; Electronic books; Electronic books